Altered neural processes underlying executive function in occupational burnout—Basis for a novel EEG biomarker - Pihlaja, Mia; Peräkylä, Jari; Erkkilä, Emma-Helka; Tapio, Emilia; Vertanen, Maiju; Hartikainen, Kaisa M. (Frontiers in Human Neuroscience, 2023)
As burnout has become a global pandemic, there is a call for improved understanding and detection of alterations in brain functions related to it. We have previously reported challenges in executive functions (EF) in daily life, especially in metacognition, in subjects with occupational burnout along with alterations in cardiac physiology. In the current study, we focused on the impact of burnout on brain physiology during a task requiring EF. Fifty-four volunteers filled in inventories of burnout, depression, and EF in daily life (BBI-15, BDI, BRIEF-A). Based on the BBI-15 score subjects were divided into burnout and non-burnout groups. Subjects performed a Go/NoGo test (Executive RT Test) engaging several EF, while their EEG was recorded. The inventory scores, cognitive performance scores, and event-related potential (N2, P3) amplitudes, latencies, and inter-peak latencies (IPL) were compared between the groups. There were significant differences in the BDI and BRIEF-A scores, with more symptoms of depression and challenges in EF in daily life in the burnout group. There were no differences in objective performance measures in the EF task. However, centroparietal P3 amplitude was larger and while there were no differences in N2 or P3 latencies, N2-P3 IPL was longer in the Go-condition in the burnout than the control group. Both ERP measures correlated significantly with burnout symptoms. A regression model from centroparietal P3 amplitude with latency and with N2-P3 IPL predicted significantly both the BBI-15 score and BRIEF-A metacognition index. We conclude that burnout is linked with challenges in EF in daily life and alterations in the underlying neural processes. While cognitive performance in the task was equal, electrophysiological measures differed between the groups. Prolonged N2-P3 IPL points towards slowed transition from one cognitive process to another. Increased P3 amplitude, on the other hand, reflects the increased allocation of neural processing resources. This may be a compensatory mechanism allowing for equal performance with controls. These electrophysiological measures, obtained during the EF task, show promise as brain physiology based biomarkers of burnout, contributing to its improved and objective detection. In addition, these results indicate burnout is linked with objective alterations in brain physiology.